-x+15-3x+6=-7x-4x

Simple and best practice solution for -x+15-3x+6=-7x-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+15-3x+6=-7x-4x equation:


Simplifying
-1x + 15 + -3x + 6 = -7x + -4x

Reorder the terms:
15 + 6 + -1x + -3x = -7x + -4x

Combine like terms: 15 + 6 = 21
21 + -1x + -3x = -7x + -4x

Combine like terms: -1x + -3x = -4x
21 + -4x = -7x + -4x

Combine like terms: -7x + -4x = -11x
21 + -4x = -11x

Solving
21 + -4x = -11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11x' to each side of the equation.
21 + -4x + 11x = -11x + 11x

Combine like terms: -4x + 11x = 7x
21 + 7x = -11x + 11x

Combine like terms: -11x + 11x = 0
21 + 7x = 0

Add '-21' to each side of the equation.
21 + -21 + 7x = 0 + -21

Combine like terms: 21 + -21 = 0
0 + 7x = 0 + -21
7x = 0 + -21

Combine like terms: 0 + -21 = -21
7x = -21

Divide each side by '7'.
x = -3

Simplifying
x = -3

See similar equations:

| (25.12^2)/(4(3.14)) | | -6/7x+17=-61 | | 7/9-5/13 | | (78x-48y)-(68x+28y)= | | -x+5y-3x-2y= | | 4(5y+7z)-28z= | | 5/13+6/11 | | 2(6y+2z)-4z= | | k+-9k-8k-10k=-20 | | 5y(2y-4)+14y= | | 9a-3(a+3)= | | 8c-10c-6=10 | | -1a-24=5a | | 2x+7(8+2x)=8 | | 6(4y+5z)-30z= | | 4log(x-6)=11 | | 16h-13h-2h-1=15 | | (25.12^2)/4(3.14) | | 52=12+4w | | -7/9(x-y+36) | | 2c-c=14 | | (80x-54y)-(62x+9y)= | | 8y-y+2y=18 | | 5(2y+4z)-20z= | | 15+3y=25 | | 4x-5/3x | | 6y(3y-4)+22y= | | (11x+23y)+(38x+50y)= | | -(2x^2-7x+7)= | | 4y(3y-6)+19y= | | A=8*(3.14) | | 4x-6=4(x+5) |

Equations solver categories